Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1242/jcs.197517
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness-dependent regulation of the SRF−Mkl1 co-activator complex requires the inner nuclear membrane protein Emerin

Abstract: The complex comprising serum response factor (SRF) and megakaryoblastic leukemia 1 protein (Mkl1) promotes myofibroblast differentiation during wound healing. SRF−Mkl1 is sensitive to the mechanical properties of the extracellular environment; but how cells sense and transduce mechanical cues to modulate SRF−Mkl1-dependent gene expression is not well understood. Here, we demonstrate that the nuclear lamina-associated inner nuclear membrane protein Emerin stimulates SRF−Mkl1-dependent gene activity in a substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
6
25
1
Order By: Relevance
“…Our results ( Fig. 5A) and those of others (Willer and Carroll, 2017), nonetheless, suggest complex and differential regulation of MKL1/SRF gene targets in LMNA deficient cells, as some genes such as VCL are repressed at steady state and not activated. Repression of some SRF targets like VCL in the face of increased MKL signaling may involve other gene specific regulatory factors.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our results ( Fig. 5A) and those of others (Willer and Carroll, 2017), nonetheless, suggest complex and differential regulation of MKL1/SRF gene targets in LMNA deficient cells, as some genes such as VCL are repressed at steady state and not activated. Repression of some SRF targets like VCL in the face of increased MKL signaling may involve other gene specific regulatory factors.…”
Section: Discussionsupporting
confidence: 71%
“…Ectopic expression of two different constitutively active MKL1 mutant proteins (Flag-MKL1-N100, lacks an N-terminal actin binding motif required for its Gactin dependent cytoplasmic retention; and Flag-MKL1-STS/A, S449, S454, and T450 mutated to A, is refractory to ERK regulated nuclear export; Muehlich et al, 2008), showed both nuclear and cytoplasmic localization ( Fig. S3), as observed by others (Willer and Carroll, 2017).…”
Section: Lmna Depleted Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…ARPC3, a member of human Arp2/3 protein complex, functions in regulating tight junctions . EMD, a serine‐rich nuclear membrane protein, functions in regulating focal adhesion . The interactions between FSCN1 and these cell–cell adhesion‐associated proteins further strengthen the roles of FSCN1 in cell adhesion.…”
Section: Discussionmentioning
confidence: 96%
“…In mammals, the LMNA gene gives rise to lamins A and C, but also minor isoforms as lamin C2 and Adelta10, by alternative RNA splicing [3], whereas B-type lamins are encoded by the LMNB1 (lamins B1) and LMNB2 (lamins B2 and B3) genes [4][5][6]. B-type lamins are ubiquitously expressed and considered essential for cell survival, whereas A-type lamins change during development and cell differentiation stages, being response to serum stimulation of cells grown on stiff substrates but was dispensable on more compliant substrates [41].…”
Section: Introductionmentioning
confidence: 99%